2016
DOI: 10.1016/j.apmr.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Improving Power and Sample Size Calculation in Rehabilitation Trial Reports: A Methodological Assessment

Abstract: To systematically assess the reporting of sample size calculation in RCTs on rehabilitation interventions for mechanical low-back pain (mLBP). Study selection We conducted an electronic database search for RCTs published from 1968 through February 2015 and included in Cochrane Systematic Reviews (SRs). Data extraction Two investigators independently applied an ad hoc six-item checklist derived from the CONSORT 2010 statement recommendations to extract data on sample size calculation. Primary outcome was the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The minority (4.2%) of randomized questions explicitly identified the delta value as the MCID with justification. These findings are in line with the limited number of previous studies investigating clinical significance reporting, wherein under-reporting was found [ 13 , 19 , 20 , 28 , 29 ]. Chan et al [ 13 ] found that, among a random sample of 27 RCTs in major medical journals, 20 articles included sample size calculations, 90% of which reported a delta value but only 11% stated that the delta value was chosen to reflect the MCID of the intervention.…”
Section: Discussionsupporting
confidence: 91%
“…The minority (4.2%) of randomized questions explicitly identified the delta value as the MCID with justification. These findings are in line with the limited number of previous studies investigating clinical significance reporting, wherein under-reporting was found [ 13 , 19 , 20 , 28 , 29 ]. Chan et al [ 13 ] found that, among a random sample of 27 RCTs in major medical journals, 20 articles included sample size calculations, 90% of which reported a delta value but only 11% stated that the delta value was chosen to reflect the MCID of the intervention.…”
Section: Discussionsupporting
confidence: 91%
“…However, in comparison to Castellini et al , who reviewed back pain trials published after 1968 and included 222 trials, we judge our search to have been comprehensive. [ 51 ]…”
Section: Discussionmentioning
confidence: 99%
“…The respective differences between the reported and replicated sample sizes were then found to range from −237.5% to 84.2%8 and −93.3% to 60.6% 9. Furthermore, there was also a discrepancy between the planned and the actually recruited number of patients (recruited sample size smaller than planned sample size: 23.6%, recruited sample size larger than planned sample size: 58.4%) 11…”
Section: Discussionmentioning
confidence: 92%